Prevalence and implications of gambling problems among firefighters. (June 2020) - Cowlishaw, S.; Little, J.; Sbisa, A.; McFarlane, A.C.; Van Hooff, M.; Lawrence-Wood, E.; O'Donnell, M.; Hinton, M.; Sadler, N.; Savic, A.; Forbes, D.; Metcalf, O.
Highlights: A significant minority of firefighters reported gambling problems (12.3%) These rates were comparable to other common mental health disorders in firefighters. Gambling problems were high relative to other addictive behaviours. Gambling problems may be a hidden issue amongst emergency service workers. Abstract: Firefighting is a high-risk occupation that accounts for vulnerability to a range of mental health problems and addictive behaviours. However, no research has addressed whether this vulnerability extends to gambling problems, and the aim of this study was thus to provide new data on frequency and implications of such problems in this occupational context. The sample consisted of n  = 566 career and retained firefighters who participated in a cross-sectional survey of an Australian metropolitan fire service. The Problem Gambling Severity Index (PGSI) was used to operationalise both clinically significant levels of problem gambling (PGSI ≥ 5), and 'at-risk' gambling (PGSI 1–4); alongside measures of major depression (PHQ-9), anxiety (GAD-7), Posttraumatic Stress Disorder (PCL-5) and alcohol problems (AUDIT), as well as other addictive behaviours, wellbeing and psychosocial issues. Results indicated 12.3% of firefighters that reported any gambling problems across a continuum of severity (PGSI ≥ 1), including 2.3% that were problems gamblers, and 10.0% reporting at-risk gambling. The weighted prevalence of problem gambling was comparable to other significant mental health conditions including depression and PTSD, while the rate of any gambling problems was high relative to other addictive behaviours. Gambling problems were associated with poor mental health and wellbeing, but not psychosocial indicators (e.g., financial difficulties). The findings suggest that gambling problems across a spectrum of severity may be significant yet hidden issues among emergency service workers, and thus require increased recognition and responses at the organisational level.